Sharing perspectives on feedback: a combined resident-faculty workshop - Bo Kim; Aishwarya Rajagopalan; Edward M. Tabasky; Sparsha S. Reddy; David R. Topor (BMC Medical Education, 2022)
Abstract Background Feedback is essential to medical education. Although the need for effective feedback delivery is well known, more recent focus is on understanding and strengthening the faculty-trainee relationship within which the feedback process is carried out. The authors developed and implemented a combined resident-faculty feedback workshop within a psychiatry residency training program to enhance participants’ understanding of challenges residents and faculty experience with the feedback process. Methods The one-hour workshop consisted of small group activities and large group discussions, focused on (i) feedback challenges for both residents and faculty and (ii) potential ways to address identified challenges. Participants completed pre-and post-workshop questionnaires to rate their level of understanding of, and answer open-ended questions regarding, feedback challenges. Mixed-methods assessment of questionnaire responses examined quantitative rating changes from pre- to post-workshop, as well as emergent qualitative themes from the open-ended responses. Results From a pool of 30 workshop participants, 26 completed each of the pre- and post-workshop questionnaires. Overall, participants were satisfied with the programming. Important considerations for the feedback process were (i) specific/constructive/timely feedback, (ii) meeting logistical/administrative feedback requirements, (iii) setting norms/expectations of effective/routine feedback, and (iv) relational/emotional considerations surrounding feedback. It appeared both faculty and residents were able to increase perspective taking about how the other group perceived the feedback process. Conclusions This pilot project is one of the first to examine a joint resident-faculty workshop focused on understanding how faculty and residents can interact to better understand each other’s perspective on the feedback process. Further work in this area is needed to identify common misperceptions and design programming to help correct them. Further research is also needed to examine the impact of such programming on the feedback process.